Utvärdering av den nationella databasen över åtgärder i vatten i fem svenska huvudavrinningsområden - Hesselgren, Jenny; Ingesdotter, Linnea (SLU/Dept. of Aquatic Sciences and Assessment, 2012)
Restoration projects are planned and carried out in order to reduce the impact due to anthropogenic influence and to achieve at least good ecological status according to the EU Water Framework Directive. The resilience effort of such restorations is however ambiguous.